The Anamorphosis Verse: A Meta-Space Framework for Understanding Perspective Transformations in Digital Visual Realms (London Journal of Research In Management & Business, 2025)
This article introduces the concept of "anamorphosis verse" as a meta-space frame work that encompasses the system of transformations, relations, and perspective shifts connecting all possible view points and visual configurations. Building upon previous research on Pixel verse (the totality of digital visual content) and Visual verse (the domain of visual meaning beyond technical materiality), this paper positions the an amorphous verse as an integrative conceptual frame work with significant implications for understanding how meaning emerges through perspective- dependent transformations rather than perspective-independent properties. Through interdisciplinary analysis drawing from semiotics, media theory, epistemology, and aesthetics, the article demonstrate show the anamorphosis verse framework offers valuable approaches to navigating increasingly complex visual environments characterized by perspective transformation rather than spectact stability.
Keywords: Chinese corporate tax system; Foreign investment; Export of Chinese products; sustainability; technology; 21st-century; innovation; CSR; Supply Chain Integration; Employee Productivity; Internal Integration; External Integration; Maritime Firms.; inequality; decomposition; minimum wage; income distribution; Blinder-Oaxaca.; Anamorphis verse; Pixel verse; Visual verse; perspective transformation; visual epistemology; digital aesthetics; anamorphosis; visual semiotics